Political regime change, economic reform and growth accelerations - Richard Jong-A-Pin; Jakob de Haan (Center for Economic Studies and ifo Institute (CESifo), 2007)
Using an improved definition and indicator of growth accelerations, we examine whether political regimes, regime changes, and economic reform are related to growth accelerations. Our results show that economic growth accelerations are preceded by economic reforms. Furthermore, we find that growth accelerations are more likely to happen after the start of a new political regime.
Keywords: O17; O11; 330; Wirtschaftswachstum; Wirtschaftsreform; Politischer Wandel; Regierungswechsel; Entwicklung; Schätzung; Welt